PERBEDAAN MINAT BELI KONSUMEN BERDASARKAN NEGARA ASAL (COUNTRY OF ORIGIN) DAN FITUR PRODUK PADA PRODUK SMARTPHONE - Priscilla Ekawati (Ma Chung Press, 2015)
This research discusses the difference purchase intention of Smartphone’s Consumer Products based on Country of Origin and Product Features. The object of this study as the name suggests is a smartphone, which is a smartphone with Country of origin from South Korea, America, China and Japan. This research is quantitative research, the data collected by survey method and using questionnaires as media, this questionnaires distributed to respondents as many as 200 people who are consumers of smartphones. Furthermore, the data is processed by using One Way ANOVA. Based on the results of One Way ANOVA test proved that there are differences in purchase intention on smartphone products based on the country of origin and there are differences purchase intention on smartphone products based on product features. In this study smartphone which country of origin is Tiongkok is the most interest for respondents. Processor speed is the first choice and the most importance for respondents to choose some smartphone. The theoretical concept about marketing can be implemented in companies which is produce or distribute products of smartphones. Country of Origin and Product Features able to attract purchase intention, especially on the smartphone product.